The Role Of The External Auditor In The Detection Of Fraud And Errors In The Financial Statements - Studying A Sample Of Auditors - Sebti, Ismail; Elguerri, Abderrahmane; Benouadah, Hachemi (جامعة الوادي - University of Eloued, 2021)
Abstract : This study aims to analyze the role of the Governor of accounts to discovery fraud and errors of the financial statements on the one hand, and on the other hand aims to know the role of these errors and fraud in rationalizing the opinion of the governor of accounts which apparent in his final report. In order to reach the objectives of the study, we used t-test for two independent samples representing the activity of the governor of accounts at the level of three Algerian states (Sétif, M'Sila and Bordj bou Arreridj) And the corresponding fraud and errors in the financial statements of the institutions under review, Backed by a series of personal interviews with accountants and executives. The study found that the governor of accounts does not detect errors and fraud in order to correct them and provide management advice, This role lies with the internal auditor, and not with the governor of the accounts, who only gives a neutral technical opinion. The role of the governor of accounts remains valid even after the date of issuing the final report, especially with regard to confidentiality, He may not give any information to relevant parties such as competitors Otherwise, he will be prosecuted. Résumé : Cette étude vise à analyser le rôle du gouverneur des comptes en matière de fraude à la découverte et d'erreurs dans les états financiers, d'une part, et d'autre part vise à connaître le rôle de ces erreurs et fraudes dans la rationalisation de l'opinion du gouverneur des comptes qui apparaît dans son rapport final. Afin d'atteindre les objectifs de l'étude, nous avons utilisé le test t pour deux échantillons indépendants représentant l'activité du gouverneur en comptes au niveau de trois États algériens (Sétif, M'Sila et Bordj bou Arreridj) Et les fraudes et erreurs correspondantes dans les états financiers des institutions examinées, étayées par une série d'entretiens personnels avec des comptables et des dirigeants. L'étude a révélé que le gouverneur des comptes ne détecte pas les erreurs et les fraudes afin de les corriger et fournit des conseils de gestion, Ce rôle incombe à l’auditeur interne et non au gouverneur des comptes qui donne seulement un avis technique neutre. Le rôle du gouverneur des comptes reste valable même après la date de publication du rapport final, notamment en ce qui concerne la confidentialité, Il ne peut donner aucune information aux parties concernées telles que les concurrents. Sinon, il sera poursuivi.
مقال
Keywords: Governor of accounts; fraud; errors; financial statements